The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/jmv.1049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a triple antigen and a single antigen recombinant vaccine for adult hepatitis B vaccination*

Abstract: Hepatitis B and its sequelae are a major public health problem. Vaccines have been available for almost 20 years; however the disease still remains a global problem. Many factors contribute to the failure to control hepatitis B, including the limited nature of the vaccination programs implemented initially. Only relatively recently has mass childhood vaccination begun to be implemented and vaccination of high-risk groups, other than healthcare workers, is still not general policy. Additional factors contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
14
1
2
Order By: Relevance
“…Its seroconversion rate reached 95.05%, a rate significantly higher than those of the other three groups. This seroconversion rate was also similar to that of the 20 μg hepatitis B vaccine reported by Young et al (2001). This similarity might be caused by the high purity of the Hansenula hepatitis B vaccine, which uses a chemosynthesis complete medium only, and not a selective medium, peptone or yeast powder.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Its seroconversion rate reached 95.05%, a rate significantly higher than those of the other three groups. This seroconversion rate was also similar to that of the 20 μg hepatitis B vaccine reported by Young et al (2001). This similarity might be caused by the high purity of the Hansenula hepatitis B vaccine, which uses a chemosynthesis complete medium only, and not a selective medium, peptone or yeast powder.…”
Section: Discussionsupporting
confidence: 84%
“…This similarity might be caused by the high purity of the Hansenula hepatitis B vaccine, which uses a chemosynthesis complete medium only, and not a selective medium, peptone or yeast powder. The seroconversion rates of the 10 μg hepatitis B vaccine produced by the North China Pharmaceutical Company and GlaxoSmithKline were slightly higher than that of the 10 μg hepatitis B vaccine previously reported by Young et al (2001). Regarding the anti-HBs GMT, the immune effects for all the vaccines were good, except those of the Shenzhen Kangtai vaccine.…”
Section: Discussionmentioning
confidence: 58%
“…Although limited data are available, small studies have reported improved seroconversion rates in obese patients with increasing needle length, dose and formulation of vaccine, and weight reduction surgery. [21][22][23][24] Other factors that have been found to correlate poorly with immune response such as smoking and age were not associated with seroconversion in our cohort. Compliance rates for hepatitis B vaccination completion varies depending on the population.…”
Section: Discussioncontrasting
confidence: 67%
“…Further, Simo Minnana et al reported lower antibody response in adolescents with high BMI when administered a three-dose regimen of recombinant hepatitis B vaccine (20). A randomized controlled trial compares triple-antigen vaccine vs standard single antigen vaccine administered in three doses over six months resulted in 71% and 95% protection rates in obese subjects when compared with lean subjects (91% & 99% respectively) (21). Therefore, the purpose of this study was to examine the correlation between body mass index, serum alanine aminotransferase activity and immunologic response in obese hepatitis B virus patients.…”
Section: Introductionmentioning
confidence: 99%